Acute neurological infections. (September 2020) - Sethi, Varun; Davies, Nicholas WS.
Abstract: Neuroinfection syndromes cause significant mortality and morbidity. Clinical syndromes include meningitis, encephalitis, mass lesion (abscess), myelitis, radiculitis, neuritis, myositis and neuromuscular junction dysfunction. Symptoms can develop rapidly (acute) or over weeks (subacute) or longer (chronic). Viruses, bacteria, fungi or protozoa can be causal. Timely diagnosis and initiation of treatment can reduce morbidity and mortality. This article briefly outlines the common acute neuroinfection syndromes. As some pathogens are more likely to be encountered in specific geographical areas, information regarding travel to, and immigration from, endemic areas must be carefully sought. Further, different populations have varied susceptibility to infection because of specific defects in the host defence as a result of co-morbidities or treatment; assessment of potential immunosuppression is mandatory in all patients presenting with neuroinfections. For more detailed discussion, UK-specific guidelines are referenced.